Will Gay and Bisexually Active Men at High Risk of Infection Use Over-the-Counter Rapid HIV Tests to Screen Sexual Partners? - Carballo-Diéguez, Alex (2012)
The Food and Drug Administration may license OraQuick(™), a rapid HIV test, for over-the-counter (OTC) sale. We investigated whether HIV-uninfected, non-monogamous gay and bisexual men who never or rarely use condoms would use the test with partners as a harm-reduction approach. Sixty participants responded to two computer-assisted self-interviews, underwent an in-depth interview, and chose whether to test themselves with OraQuick(™). Over 80% of the men said they would use the kit to test sexual partners or themselves if it became available OTC. Most participants understood that antibody tests have a window period in which the virus is undetectable yet saw advantages to using the test to screen partners; 74% tested themselves in our offices. Participants offered several possible strategies to introduce the home-test idea to partners, frequently endorsed mutual testing, and highlighted that home testing could stimulate greater honesty in serostatus disclosure. Participants drew distinctions between testing regular versus occasional partners. Non-monogamous MSM who never or rarely use condoms may nevertheless seek to avoid HIV. Technologies that do not interfere with sexual pleasure are likely to be used when available. Studies are needed to evaluate the advantages and disadvantages of using OTC rapid HIV tests as one additional harm-reduction tool.